Synergistic Cytotoxicity of Cisplatin Combined with Curcumin and Green Tea Extract via Nanoliposomal Co-Delivery in Oral Squamous Cell Carcinoma - Yousefi, Mahsa; Vejdani, Mohammadreza; Esmaeili, Ladan; Hasanzade, Seher; Foziljonova, Malika; Yarmuxamedova, Makhbuba; Tojiboyeva, Yoqutkhon; Toirov, Otabek; Odilov, Xurshidjon; Khakimova, Bakhor; et al. (Asian Pacific Journal of Cancer Biology, 2026)
Background: Oral squamous cell carcinoma (OSCC) remains one of the most prevalent malignancies worldwide, with cisplatin-based chemotherapy limited by systemic toxicity and drug resistance. The present study aimed to enhance cisplatin efficacy through nanoliposomal co-delivery with natural antioxidants curcumin (Cur) and green tea extract (epigallocatechin gallate, EGCG). Methods: Nanoliposomes were prepared via the thin-film hydration technique followed by sonication and extrusion, generating six formulations: cisplatin-loaded (L-Cis), curcumin-loaded (L-Cur), green tea extract-loaded (L-EGCG), cisplatin + curcumin (L-Cis/Cur), cisplatin + green tea extract (L-Cis/EGCG), and triple co-loaded nanoliposomes containing cisplatin, curcumin, and EGCG (L-Cis/Cur/EGCG) prepared according to a 1:6:6 molar ratio. Results: Physicochemical characterization revealed nanoscale particle size (212–279 nm), uniform distribution (PDI < 0.3), negative zeta potential (−19 to −23 mV), and high encapsulation efficiencies (69–84%). Scanning electron microscopy confirmed spherical morphology with smooth, homogeneous surfaces. The MTT assay demonstrated that co-loaded and triple-loaded liposomes exhibited significantly higher cytotoxicity than single-drug formulations (p < 0.001). While L-Cis reduced cell viability to approximately 50%, L-Cur and L-EGCG showed moderate effects ( 65–70% viability). Co-formulations (L-Cis/Cur and L-Cis/EGCG) further decreased viability to 25–30%, and the triple co-loaded L-Cis/Cur/EGCG (1:6:6) formulation induced the strongest cytotoxic response, consistent with synergistic drug interaction. Live/Dead fluorescence imaging corroborated these findings, showing an elevated proportion of PI-positive apoptotic cells in the co-delivery groups, particularly in the triple-loaded syste. Conclusion: Collectively, these results demonstrate that nanoliposomal co-encapsulation of cisplatin with curcumin and green tea extract enhances cytotoxic efficacy and apoptotic activity in OSCC cells compared to single-agent systems. The optimized L-Cis/Cur/EGCG (1:6:6) formulation exhibited the most favorable physicochemical properties and biological performance, highlighting its potential as a synergistic nanocarrier platform for oral cancer therapy with improved efficacy and reduced systemic toxicity.